Negative play contagion in calves - Größbacher, Verena; Lawrence, Alistair B; Winckler, Christoph; Špinka, Marek (Scientific reports, 2020)
Play is a strong outwardly directed, emotional behaviour and can contagiously spread between individuals. It has been suggested that high-playing animals could 'seed' play in others, spreading positive affective states. Despite the current interest in play contagion there has been no previous attempt to measure the strength of the play contagion effect. The calf (Bos taurus) is ideal for testing the strength of play contagion as play in calves is strongly related to energy intake from milk. We manipulated play in calves through their milk allowances and housed the calves in uniform groups all on the same milk allowance (high = UHigh or low = ULow) or in mixed groups with calves in the same group receiving either a high (= MHigh) or low (= MLow) milk allowance. We measured locomotor play using accelerometers on two consecutive days when calves were four and eight weeks old, in order to study play contagion over a protracted developmental window. We anticipated that differences in the level of play contagion between treatment groups would result in difference in the play levels observed in the MLow and ULow individuals. Contrary to our expectations we found that spontaneous play was suppressed in the high-milk calves housed in mixed groups (MHigh), in comparison to calves housed with group mates all receiving high-milk (UHigh). These results are the first to quantify a negative play contagion effect, particularly in a situation of long-term contact, and may suggest that negative contagion has a stronger effect on play behaviour than positive contagion.
Keywords: Behavior, Animal; mléko; dieta; Animals, Newborn; Housing, Animal; bydlení zvířat; mužské pohlaví; energetický příjem; Energy Intake; novorozená zvířata; skot; ženské pohlaví; zvířata; Humans; chování zvířat; Cattle; hra a hračky; Milk; Diet; Female; Play and Playthings; lidé; Male; Animals